Natural Sources and Anthropogenic Influences on the River Water and Groundwater Chemistry of the Lower Mahanadi Basin: Insights From Radiogenic Sr Isotopes and Major Ion Chemistry - Acharya, Shiba Shankar; Hishamunda, Valens; Chakrabarti, Ramananda (Frontiers in Water, 2022)
The Mahanadi River ranks second among the rivers in the peninsular India in terms of water potential and flows through a geologically heterogeneous terrain. The present study uses a multiproxy approach, involving concentrations of major ions, and 87Sr/86Sr of the dissolved phases in seasonally collected river water and groundwater samples from the Lower Mahanadi Basin to investigate the sources of ions, the Cl-enrichment in the river water, the influences of the man-made structures like the Naraj Barrage, and the role of fertilizers on the chemistry of the river water. This study also provides the first estimates of the radiogenic Sr-flux of the Mahanadi River to the Bay of Bengal. Both the inverse and forward models were used to evaluate the contributions from different sources to the dissolved ions of the Mahanadi River. The results suggest that even in the predominantly silicate watershed of the Lower Mahanadi River, the riverine chemistry is modulated primarily by the carbonate dissolution followed by the silicate weathering. The Naraj Barrage, which divides the main channel of the Lower Mahanadi River into several distributaries marks a divide between the less polluted upper stream and the more polluted downstream. The radiogenic 87Sr/86Sr of the Mahanadi River water can be explained by the mixing of four endmembers: Proterozoic carbonates, Archean silicates, rainwater, and fertilizers. The dominance of agricultural input during monsoon is consistent with high loadings of nitrates and phosphates used as fertilizers in the Mahanadi River basin along with a strong positive relationship between phosphate and 87Sr/86Sr of the river waters. The flux-weighted averages of Sr concentration and 87Sr/86Sr to the Bay of Bengal were found to be 1.03 mol/l and 0.72154, respectively. The groundwater composition of the Lower Mahanadi Basin is modulated by the mixing of four endmembers, viz. weathering of silicate and carbonate rocks, the mixing of Bay of Bengal seawater and fertilizer inputs. The average Sr concentrations of the groundwater samples of the Mahanadi basin is 5.45 mol/l having an average 87Sr/86Sr ratio of 0.71772.